2022
DOI: 10.3390/ijms23126519
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Heparan Sulfate in CCL26-Induced Eosinophil Chemotaxis

Abstract: Proinflammatory chemokine ligand 26 (CCL26, eotaxin-3) mediates transendothelial cell migration of eosinophils by binding and activating the G-protein-coupled (GPC) chemokine receptor 3 on the surface of eosinophilic cells. Here we have investigated the role of glycosaminoglycans (GAGs) as potential co-receptors in the process of CCL26-induced eosinophil chemotaxis. For this purpose, we have first identified the GAG-binding site of CCL26 by a site-directed mutagenesis approach in the form of an alanine screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…As both chemokines have similar HS binding but different TNC binding affinities, we speculate that TNC acts as an attenuator in monocyte (PBMC) and as an amplifier in eosinophil mobilization by preventing CCL2 from binding to HS on the one hand and by enabling CCL26 to bind to HS on the other [62,63]. This is supported by our recent finding that HS on monocytes as well as eosinophils is important for chemotaxis [52,53]. The different TNC binding affinities of the two chemokines might thus suggest different binding sites on TNC.…”
Section: Chemotaxissupporting
confidence: 70%
See 1 more Smart Citation
“…As both chemokines have similar HS binding but different TNC binding affinities, we speculate that TNC acts as an attenuator in monocyte (PBMC) and as an amplifier in eosinophil mobilization by preventing CCL2 from binding to HS on the one hand and by enabling CCL26 to bind to HS on the other [62,63]. This is supported by our recent finding that HS on monocytes as well as eosinophils is important for chemotaxis [52,53]. The different TNC binding affinities of the two chemokines might thus suggest different binding sites on TNC.…”
Section: Chemotaxissupporting
confidence: 70%
“…We have recently shown that GAGs present on target immune cells contribute to chemotaxis, in addition to GAGs located at the site of vessels where immune cells extravasate into affected tissues [52,53]. Chemokine secretion, immobilization, and receptor activation are apparently mediated by GAGs situated on both sites of the immunological reaction, that is, on the epithelial/endothelial vessel cells as well as on the blood-resident immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Chemokine ligand 26 (CCL26) interacts with CCR3 to attract eosinophils to sites of in ammation [13] and mediates trans-endothelial migration of eosinophils by binding to and activating G protein-coupled (GPC) chemotaxis of CCR3 on the surface of eosinophils [14]. It was found that signi cantly elevated levels of the CCL26 gene were found in eosinophilia-related diseases.…”
Section: Discussionmentioning
confidence: 99%